Hubungan Antara Efikasi Diri Dengan Kecemasan Menghadapi Dunia Kerja Pada Siswa Smk Muhammadiyah Karanganyar - Nuzulia Rahmawati, Septi; , Achmad Dwityanto, S.Psi, M.Si (2017)
Relationship Between Self Efficacy With Anxiety Facing the World of Working Students SMK Muhammadiyah Karanganyar ABSTRACT The high unemployment rate, especially the graduates of SMK with a percentage of 9.84 percent raises its own concern for students of SMK especially class XII who will enter the workforce. This raises the anxiety of anxiety related to a career for fear of failure in the workplace. One of the factors that affect the anxiety of facing the work world is self efficacy. This study aims to determine the relationship between self efficacy with anxiety against the world of work. Hypothesis proposed that there is a negative relationship between self efficacy with anxiety facing the world of work. Sampling technique in this research is cluster random sampling counted 60 people. This research uses quantitative method by using measuring instrument of self efficacy scale and anxiety to face work world. Data analysis in this study using SPSS 16.0 by using product moment correlation, obtained correlation coefficient r -0,518 with significance p = 0,000 (p≤0,01), which means there is a very significant negative relationship between self efficacy with anxiety facing the world Work on vocational students. High self efficacy category is indicated by (RE) 89,65 >(RH) that is 72. While category of anxiety face work world is very low this is indicated by (RE) 62,87l <(RH) of 122.5. Effective contribution of self efficacy with anxiety to face the working world of 26,8% can be obtained from the determinant coefficient (r2) of 0.268. This shows that there are other factors of 73,2% that affect the anxiety of facing the world of work outside of self efficacy. Keywords: self efficacy, anxiety against the world of work